Far-Reaching Dispersal of Borrelia burgdorferi Sensu Lato-Infected Blacklegged Ticks by Migratory Songbirds in Canada - John D. Scott; Kerry L. Clark; Janet E. Foley; Bradley C. Bierman; Lance A. Durden (Healthcare, 2018)
Lyme disease has been documented in northern areas of Canada, but the source of the etiological bacterium, Borrelia burgdorferi sensu lato (Bbsl) has been in doubt. We collected 87 ticks from 44 songbirds during 2017, and 24 (39%) of 62 nymphs of the blacklegged tick, Ixodes scapularis, were positive for Bbsl. We provide the first report of Bbsl-infected, songbird-transported I. scapularis in Cape Breton, Nova Scotia; Newfoundland and Labrador; north-central Manitoba, and Alberta. Notably, we report the northernmost account of Bbsl-infected ticks parasitizing a bird in Canada. DNA extraction, PCR amplification, and DNA sequencing reveal that these Bbsl amplicons belong to Borrelia burgdorferi sensu stricto (Bbss), which is pathogenic to humans. Based on our findings, health-care providers should be aware that migratory songbirds widely disperse B. burgdorferi-infected I. scapularis in Canada’s North, and local residents do not have to visit an endemic area to contract Lyme disease.